Health seeking behaviour among construction workers in Kancheepuram district, Tamil Nadu: a descriptive study - Kumar P., Mohan; S., Gopalakrishnan (International Journal Of Community Medicine And Public Health, 2020)
Background: Construction workers form the second largest working group in the un-organized sector and their life depends on the daily wages they earn. This study was planned to assess the health seeking behaviour of construction workers in an urban area of Kancheepuram District in Tamil Nadu. Methods: This descriptive cross-sectional study was done among 302 male construction workers by random sampling from four construction sites using a pre-tested structured questionnaire. Data collected was analysed using SPSS Version 21 software and the result presented using descriptive statistics. Institutional ethical committee approval and informed consent were obtained. Results: Among construction workers, nearly 55% belonged to less than 40 years age. Majority were illiterates and more than half of them were working as helpers for masons, painters and centring workers. About 63.9% were smokers, 62.9% consuming alcohol and 57.6% use other form of tobacco. Nearly 69.9% were pre-hypertensive and 15% were hypertensive. About 87.4% had normal BMI, 5.3% were underweight and 7% were overweight. Nearly 78.8% of workers sought medical care and they preferred allopathic system (97.7%) for treatment. 87.4% preferred treatment from private hospitals while 8.8% preferred to get treatment at the construction site itself and remaining goes to government hospitals for treatment. Most workers (95.0%) preferred outpatient’s treatment. Conclusions: Majority of construction workers prefer private allopathic medical facilities for their medical treatment, even though it adds to their out of pocket expenditure. There seems to be a knowledge gap, convenience and financial burden in their health seeking behaviour.